2017
DOI: 10.12691/ajnr-5-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Women Satisfaction with Family Planning Services in Maternal and Child Health Centers, Assiut City, Egypt

Abstract: Family planning (FP) is critical for the health of women and their families, and it can accelerate a country's progress toward reducing poverty and achieving development goals. FP is an important component of primary health care, maternal and child health. It is the means of planning families that want space according to choice and time to fit in with life decisions. Aim: This study aimed to assess satisfaction level of women attending Maternal and Child Health (MCH) centers with FP services. Methods: Descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
1
5
0
1
Order By: Relevance
“…First and second, Mohamed S et al (2017) and a previously mentioned study by Nasr and Hassan (2016) found that the majority of the women were highly satisfied with the total quality of the process of FP services provision. The former described the Egyptian women's satisfaction with FP services in MCH centers.…”
Section: Discussionmentioning
confidence: 78%
“…First and second, Mohamed S et al (2017) and a previously mentioned study by Nasr and Hassan (2016) found that the majority of the women were highly satisfied with the total quality of the process of FP services provision. The former described the Egyptian women's satisfaction with FP services in MCH centers.…”
Section: Discussionmentioning
confidence: 78%
“…Study shows weaknesses in the infrastructure of services, such as the lack of human resources and deficient structure of health facilities, negatively impacting the child's development (29) . However, when evaluating maternal and child health centers in Egypt, the level of quality in the organization of services and facilities available in clinics was considered good; and it has been proven that women's satisfaction is affected by the following factors: parity number, family income, as well as health professional care (30) .…”
Section: Discussionmentioning
confidence: 99%
“…Still, in Brazil, there is no adequate implementation in the daily routine of primary care services, making care a challenge, with the need to work integrally in the process (29)(30)(31) . This is reaffirmed in an international study whose objective was to identify the health promotion of primary care professionals, which showed a concentration of individual practices; however, there is little evidence on the best approaches to providing preventive care and improving health, and little attention is given in the literature to examining the impact of the organizational context on the way services are provided or on how it influences the efficiency of health improvement interventions (32) .…”
Section: Discussionmentioning
confidence: 99%
“…Evidencia-se importante avanço no que se refere à indução de saberes e práticas qualificadoras da saúde materno-infantil, embora a redução das taxas de mortalidade materna e neonatal sigam lentas em âmbito de Brasil. Estudos (BRANDT et al, 2021, AHMED MOHAMED;GHAREEB MOHAMED;FOUAD ARIEF, 2017) demonstram que os primeiros 28 dias do recém-nascido, em ambiente domiciliar, merecem atenção especial. O foco, no entanto, não pode centrar-se apenas no recémnascido, mas também na mãe que, igualmente, demanda cuidados singulares.…”
Section: Acolhendo àS Singularidadesunclassified